The Results of Clinical Trials of Recombinant Vaccine Virus, MVA Strain, Expressing Genes of Human Immunodeficiency Virus - L. F. Stovba (Проблемы особо опасных инфекций, 2021)
Although successes in antiretroviral therapy (ART) turned AIDS from lethal illness into sluggishly progressing disease, its prevention and treatment remain one of the most socially significant concerns. The increase in the number of patients infected with human immunodeficiency virus (HIV), especially in the USA, South America and Europe, determines the need in creating a vaccine against this disease. Existing vaccination practice has demonstrated efficiency of priming/boosting scheme for the development of immune responses. As anti-vector immunity of priming vector can constrain the response to boosting immunization with the same vaccine, heterologous priming/boosting vector constructs are used. An ideal AIDS vaccine would prevent virus dissemination and control viral replication, but it also must be safe for HIV-infected contingent. The vaccination of HIV-infected individuals is used for enhancing immune-mediated elimination of persistently HIV-infected CD4+ Т-cells during long-term ART in order to purge the latently infected viral reservoirs. The paper considers the results of clinical trials of DNA-anti-HIV/AIDS vaccines and recombinant MVA strain of vaccinia virus, expressing different combination of HIV genes, which demonstrated the safety and tolerability both, in HIV-infected and non-HIV-infected volunteers. All implemented schedules of vaccination induced cell-mediated and humoral immune responses in all volunteers. And though there are no data on acquiring AIDS by HIV-uninfected volunteers from groups at low risk of HIV-infection, there are no grounds to conclude the sufficiency of induced protection for the prevention of possible HIV infection.